A Case Report of Post-Operative Jöd-Basedow Phenomennon Following Oral and IV Iodine Contrast Administration - Maureen Higgs; Erroll Hull; Eugenio Lujan (Case Reports in Endocrinology)
This is a case of thyrotoxicosis, due to the Jöd-Basedow phenomenon following administration of oral and IV iodinated contrast in a patient with history of gastrointestinal stromal tumor (GIST) and small bowel obstruction. The patient developed atrial fibrillation and had an extended stay in the intensive care unit. Given the aging population with possible subclinical hyperthyroidism, multinodular goiter, and the rise in contrast administration for routine diagnostic studies, this case serves to raise awareness of the risks of “routine” tests administered to our aging patient population.